The Culture of Responsibility of a University as the Factor Stimulating Implementation of the Principles of Sustainable Development by Entrepreneurs and Consumers - Drelich-Skulska, Bogusława; Sobocińska, Magdalena; Domiter, Małgorzata (Publishing House of Wroclaw University of Economics and Business, 2024)
The aim of this section was to present the role of universities in shaping a responsible society, and extend the scope of the implementation of sustainable development principles by entrepreneurs and consumers. Particular attention was paid to a university’s responsibility culture, a factor which conditions the implementation of the sustainable development concept not only in the university itself but also by its stakeholders. This requires including the category of sustainable development in many areas related to the university’s functioning, including scientific research, commercialisation of its results, educational concepts and programmes, and also managing the university itself. The considerations presented in this chapter centred on the evolution of functions and tasks performed by universities, as well as indicated in what way they can participate in the realisation of the aims of sustainable development, and stimulate entrepreneurs and consumers to behaviour based on the model of the economics of moderation. The study was based on an extended literature review and analysis of practices developed in WUEB, where the strategic approach to shaping the culture of responsibility is applied.
Drelich-Skulska, B., Sobocińska, M., & Domiter, M. (2024). The Culture of Responsibility of a University as the Factor Stimulating Implementation of the Principles of Sustainable Development by Entrepreneurs and Consumers. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 17-31). Publishing House of Wroclaw University of Economics and Business.
Keywords: sustainable development; universities; culture of responsibility; green competencies